Modelo matemático para analisar o controle de insetos-praga em consórcio de culturas com antibiose - Dalmolin, Laura (2017)
In this work, we propose a Coupled Map Lattices model to analyze the dynamics of an insect-pest in intercropping of a main culture (target of the herbivore) with a secondary culture that presents antibiosis resistance to this insect. We analyzed two main factors: the effects of the secondary crop area and its distribution in the domain on the insect-pest dynamics. The reduction in the population density of insects caused by these factors is described by a percentage of the population decrease. By means of a discrete model for a single species, we verified that the presence of the secondary crop reduces the density of individuals in the main crop and that this reduction depends on the spatial distribution and degree of resistance of the secondary crop, besides the type of movement of the insect. When considering a discrete host-parasitoid model, we observed that the secondary culture also reduces the density of parasitoids, so that the use of this control strategy should be evaluated according to the problem under study. In general, the distribution of the secondary crop in stripes was the spatial arrangement that presented better results for the control of the insect-pest.